Effects of photobiomodulation therapy on regulation of myogenic regulatory factor mRNA expression in vivo: A systematic review. Issue 2 (6th December 2021) - Shepherd, David W.; Norris, Joseph M.; Simpson, Benjamin S.; Player, Darren J.; Whitaker, Hayley C.
Abstract: Non‐invasive promotion of myogenic regulatory factors (MRFs), through photobiomodulation therapy (PBMT), may be a viable method of facilitating skeletal muscle regeneration post‐injury, given the importance of MRF in skeletal muscle regeneration. The aim of this systematic review was to collate current evidence, identifying key themes and changes in expression of MRF in in vivo models. Web of Science, PubMed, Scopus and Cochrane databases were systematically searched and identified 1459 studies, of which 10 met the inclusion criteria. Myogenic determination factor was most consistently regulated in response to PBMT treatment, and the expression of remaining MRFs was heterogenous. All studies exhibited a high risk of bias, primarily due to lack of blinding in PBMT application and MRF analysis. Our review suggests that the current evidence base for MRF expression from PBMT is highly variable. Future research should focus on developing a robust methodology for determining the effect of laser therapy on MRF expression, as well as long‐term assessment of skeletal muscle regeneration. Abstract : Low‐lever laser therapy (LLLT) has shown to promote soft tissue healing through attenuating inflammation and promoting expression of myogenic regulatory factors (MRFs). MRFs facilitate myogenic lineage development and maturation into muscle fibres to repair damaged tissue. LLLT enhanced the expression of associated MRFs through the myogenic process. Myogenic determination factor 1 shows the most positive response to LLLT. Laser therapy can potentially assist in the repair of damaged tissue, though optimal dosimetric parameters are yet to be established.